Should all other biologists follow the lead of virologists and stop italicizing the names of living organisms? A proposal - Calisher, Charles H.; van Regenmortel, Marc H. V. (Zootaxa, 2009)
As thousands of viruses were discovered over the years, they were given common names in English and in other languages. Then, about 20 years ago, the category “species” was introduced in virology and the vernacular names of viruses were adopted for use as species nomina and were italicized to indicate that they then referred to taxonomic entities. As a result, virologists should write that a patient was infected “with measles virus” but not “with the species Measles virus” nor with “the genus Morbillivirus”, since taxonomic classes cannot cause infections. In other fields of biology the great majority of organisms only have Latin species nomina, written in italics, and no vernacular name. As a result, it will be said that a patient was infected with Bacillus anthracis, as though that taxonomic entity were able to cause a disease. What is meant, of course, is that the infection was caused by a bacterium that is a member of the species Bacillus anthracis. Attributing the infection to a species instead of an organism arises because of the absence of vernacular names for many organisms. However, this logical muddle could be avoided if the writer would use the species nomina of the disease-causing organisms but wrote them in unitalicized Roman letters, as is done with viruses. To do away with logically ill-formed statements, we propose that the names of all biological entities for which there is no common name be derived from the species nomen but written in unitalicized Roman letters. The italicized style would then be reserved for the species to which the entity belongs.